2012
DOI: 10.1371/journal.pone.0048220
|View full text |Cite|
|
Sign up to set email alerts
|

High-Fat Diet Induces Periodontitis in Mice through Lipopolysaccharides (LPS) Receptor Signaling: Protective Action of Estrogens

Abstract: BackgroundA fat-enriched diet favors the development of gram negative bacteria in the intestine which is linked to the occurrence of type 2 diabetes (T2D). Interestingly, some pathogenic gram negative bacteria are commonly associated with the development of periodontitis which, like T2D, is characterized by a chronic low-grade inflammation. Moreover, estrogens have been shown to regulate glucose homeostasis via an LPS receptor dependent immune-modulation. In this study, we evaluated whether diet-induced metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 46 publications
4
53
0
1
Order By: Relevance
“…Furthermore, periodontal diseases themselves could be modulated by alteration of gut microbiota-induced systemic inflammation. In support of this hypothesis, it has been reported that high-fat diet-induced obesity increased alveolar bone resorption, a characteristic feature of periodontitis4445.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, periodontal diseases themselves could be modulated by alteration of gut microbiota-induced systemic inflammation. In support of this hypothesis, it has been reported that high-fat diet-induced obesity increased alveolar bone resorption, a characteristic feature of periodontitis4445.…”
Section: Discussionmentioning
confidence: 78%
“…It was also suggested that estrogen-like compounds may be metabolized by gut microbes to produce estrogenic metabolites that could affect the immune system (Chen and Madak-Erdogan, 2016). High fat diets were shown to increase the lipopolysaccharide (LPS) producing Gram-negative bacteria, whereas estrogen was reported to reduce LPS-induced inflammation and decrease the concentration of these bacteria (Blasco-Baque et al, 2012). While further experiments are needed to determine whether the microbiota composition, which was observed in estrogen-treated mice is sufficient to induce protection against EAE, these findings point to a feedback loop between sex hormones and gut microbiota that affects the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the potential mechanisms of periodontal inflammation and nutritional factors provided advice on how to be healthy by encouraging the consumption of fruit and vegetables (which contain antioxidants) fish oil (which contains omega‐3 polyunsaturated fats), and emphasized the risk of diets that are high in refined carbohydrates . The results of an experiment performed in animals showed that a high‐fiber, low‐fat diet improves periodontal disease markers , and another study showed that a high‐fat diet was associated with worsening periodontal disease . Furthermore, serum albumin, which is considered to be an index of nutritional status, has been found to be negatively correlated with periodontal disease .…”
mentioning
confidence: 99%